El relato mapuche como elemento para promover la comprensión lectora y la convivencia intercultural - Sánchez Correa, Elena; Díaz del Valle, Lucía; Ow González, Maili (Didáctica. Lengua y Literatura, 2007)
This article is the outcome of research carried out at the Faculty of Education of the Pontifical Catholic University of Chile in 2005. It was entitled «Dialogic interaction with multicultural literary texts as a means to encourage harmonious coexistence within diversity». This paper starts with a brief introduction followed by theoretical background on intercultural education, Mapuche culture and narrative, social understanding and reading comprehension. It continues with a description of the process of selection of Mapuche narrative. The authors also propose didactic guidelines to encourage reading comprehension and intercultural coexistence. As an example, the article also includes a Mapuche story – El Sumpall – and suggests methodological guidelines to use with students. L’article est le résultat d’une recherche réalisée dans L’université «Pontificia Universidad Católica du Chili», –Faculté d’Éducation– pendant l’année 2005. Son titre était «L’interaction dialogique avec des textes littéraires pluriculturelles pour favoriser une convivialité harmonique dans la diversité» L’écrit, à la suite d’une brève introduction, propose des références théoriques sur l’éducation interculturelle, la culture Mapuche et ses récits, la convivialité harmonique et la comprensión lectrice. Ensuite, il décrit le processus suivi pour sélectionner les récits du peuple Mapuche et propose une approche didactique dans la finalité de promouvoir la compréhension lectrice et la convivialité interculturelle. Comme exemple, on trouvera y inclus le récit Mapuche «El Sumpall» et la proposition de travail avec les étudiants.